Fuel cell technology for domestic built environment applications: state of-the-art review - Elmer, Theo; Worall, Mark; Wu, Shenyi; Riffat, Saffa (Elsevier, 2015)
Fuel cells produce heat when generating electricity, thus they are of particular interest for combined heat and power (CHP) and combined cooling heat and power (CCHP) applications, also known as tri-generation systems. CHP and tri-generation systems offer high energy conversion efficiency and hence the potential to reduce fuel costs and CO2 emissions. This article serves to provide a state-of-the-art review of fuel cell technology operating in the domestic built environment in CHP and tri-generation system applications. The review aims to carry out an assessment of the following topics: (1) the operational advantages fuel cells offer in CHP and tri-generation system configurations, specifically, compared to conventional combustion-based technologies such as Stirling engines, (2) how decarbonisation, running cost and energy security in the domestic built environment may be addressed through the use of fuel cell technology, and (3) what has been done to date and what needs to be done in the future. The article commences with a review of fuel cell technology, then moves on to examine fuel cell CHP systems operating in the domestic built environment, and finally explores fuel cell tri-generation systems in domestic built environment applications. The article concludes with an assessment of the present development of, and future challenges for, domestic fuel cells operating in CHP and tri-generation systems. As fuel cells are an emergent technology the article draws on a breadth of literature, data and experience, mostly from the United Kingdom, Germany, Japan, America and Australia.